Contemporary Interventional Ultrasonography in Urology - Ukimura, Osamu (Springer, 2017)
Contemporary Interventional Ultrasonography in Urology is a comprehensive resource for all practicising urology clinicans, as well as trainees wanting to learn the current state-of-the-art. This book offers detailed, all-inclusive reviews of every useful topic, while also significantly showing how they each fit into the grander context of urological imaging in general. Exciting new developments and applications of imaging techniques have emerged over the last few years, leading to many improvements to the diagnosis and staging of urologic diseases. Refinements in the technology mean that imaging now is much more precise than even 5 years ago, and this has significantly enhanced its application within several key fields. As such, there are no other books currently available that cover these advances’ impact on the discipline of urology. Contemporary Interventional Ultrasonography in Urology brings together the latest scientific advances in this technology, highlighting a variety of common urological problems which would benefit from further ultrasonography work, either as a diagnosing tool or as an accompaniment to surgery. Featuring contributions from an international range of leading experts, and edited by two renowned field-leaders, and with an attractive layout and a variety of useful illustrations, this book will be a must-have on urologic interventional ultrasonography for both the aspiring student and the practising professional alike.